The effect of relationship marketing, emotional marketing and supportive marketing on customers loyalty with the mediating role of customers satisfaction: a case study (pars Abad banks) - Talaneh, Elhameh; Sarboland, Kheirollah (International Journal of Scientific World, 2017)
In today’s competitive world, the attraction and retention of customers in banking industry has become much more difficult and only those banks are successful in this competition that focuses their activities on attraction and retention of their customers. In other words, customers’ satisfaction and loyalty are considered as one of the most significant objectives of banking system. Consequently, the purpose of present research is to investigate the impact of relationship marketing, emotional marketing and supportive marketing on the customers’ loyalty in Pars Abad banks with the mediating role of customers’ satisfaction. The statistical population of research comprises all the customers of private banks, public banks and credit and finance institutions of Pars Abad. From this population, 377 customers were selected as the research sample using random sampling method in terms of Morgan table. The questionnaires were used as the statistical instrument for data collection. The reliability of these questionnaires was confirmed using Cranach’s Coefficient Alpha. The collected data were analyzed using Structural Equation Modeling (SEM) and Boot Strap. The SPSS, Lisrel and Stata software were also used in various stages of estimation. The results revealed that the customers’ satisfaction plays a mediating function in the relationship between the effect of relationship marketing, emotional marketing and supportive marketing on customers’ loyalty.